2009
DOI: 10.1063/1.3212449
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical predictions of adsorption behavior of elements 112 and 114 and their homologs Hg and Pb

Abstract: Fully relativistic (four-component) density-functional theory calculations were performed for elements 112 and 114 and their lighter homologs, Hg and Pb, interacting with gold systems, from an atom to a Au(n) cluster simulating the Au(111) surface. Convergence of the adatom-metal cluster binding energies E(b) with cluster size was reached for n>90. Hg, Pb, and element 114 were found to preferably adsorb at the bridge position, while element 112 was found to preferably adsorb at a hollow site. Independently of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
87
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(109 citation statements)
references
References 43 publications
21
87
1
Order By: Relevance
“…This strongly supports the above mentioned conclusion about the high volatility of Cn and its metallic character expressed in a clear -but weaker than Hg -metal-metal bond formation with Au. All experimental findings [249], are in agreement with a fullyrelativistic 4-c DFT calculation [84,239]. Details on the discussion of extrapolated and theoretically calculated sublimation enthalpies can be found in [84,239,249,250].…”
Section: Copernicium (Cn Element 112)supporting
confidence: 70%
See 1 more Smart Citation
“…This strongly supports the above mentioned conclusion about the high volatility of Cn and its metallic character expressed in a clear -but weaker than Hg -metal-metal bond formation with Au. All experimental findings [249], are in agreement with a fullyrelativistic 4-c DFT calculation [84,239]. Details on the discussion of extrapolated and theoretically calculated sublimation enthalpies can be found in [84,239,249,250].…”
Section: Copernicium (Cn Element 112)supporting
confidence: 70%
“…Relativistic calculations, which show a strong stabilization of the closed 7s 2 shell, indicated the possibility that element 112 is rather inert -almost like a noble gas -and, in elementary form, a gas or a very volatile liquid (metal) [141]. Recent calculations [84,[237][238][239] (and [240] with somewhat different results) predict that a very volatile Cn would still retain a metallic character which would allow bond formation with metallic surfaces like Au [84,239]. On inert surfaces, however, no adsorption is expected [84,238].…”
Section: Copernicium (Cn Element 112)mentioning
confidence: 99%
“…21 Thus, Cn exhibits noble-metal-like properties 18,19 , in line with trends established by the lighter homologues in group 12, and in good agreement with recent theoretical calculations. 14,15 In recent years, Fl isotopes with half-lives of the order of seconds have been discovered. 9,[22][23][24][25][26] The most long-lived currently known Fl isotopes, produced in the nuclear fusion reaction 48 Ca + 244 Pu, are 289 Fl (T 1/2 = 2.1 s) and 288 Fl (T 1/2 = 0.69 s), which are formed upon the evaporation of three or four neutrons from the excited compound nucleus, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…3͒ is much lower than that derived from the experimental measurements, 1.02Ϯ 0.03 eV. 7 Taking into account small equilibrium Cn-Au separations in the cluster models of adsorption complexes 3,5,8 and rather high orbital energies for the filled 6d-shell of E112, one can expect quite large d 10 -d 10 contributions to the Cn-Au bonding ͑an analogy with the aurophilic attraction 12 might be pertinent͒. Since the Coulomb correlations between nonoverlapping subsystems ͑that is, London dispersion forces͒ cannot be correctly included in the generalized gradient ͑GGA͒ and GGA-based hybrid exchange-correlation functionals ͑XCFs͒, 13,14 the DFT techniques employing these approximations are problematic if such interactions are important.…”
Section: Introductionmentioning
confidence: 89%
“…1 and 2͒ inspired numerous theoretical studies of Cn-Au interactions ͑see, e.g., Ref. 3 and references therein; a recent review can be found in Ref. 4͒.…”
Section: Introductionmentioning
confidence: 99%